The Effectiveness of the Computer Training Courses as Perceived by the Teachers in Enhancing Their Computer Skills - Lim, Siew Geck (1999)
The purpose of the study was to describe the effectiveness of the computer training courses as perceived by the teachers in enhancing their computer skills. A set of questionnaires was administered to 80 primary and secondary teachers who have undergone the two weeks master trainer computer courses. Data collected was analysed in three factors, namely, 1. Beginning Level of Computer Skills, 2. Advanced Level of Computer Skills, and 3. Training management. All the factors were analysed by using descriptive statistics in terms of frequencies, percentages, means, and standard deviations. T-test was also used in the data analysis as inferential statistics in determining the differences between the variables. Findings revealed that teachers perceived the computer training courses to be relatively effective in enhancing their beginning level computer skills as compared to the advanced level. They also perceived some aspects of the training management to be rather unsatisfactory particularly in terms of frequency and the duration of the training. The results of t-test indicate that teachers' perceived training effectiveness in enhancing their computer skills is significantly different in terms of gender, academic qualification, and computer experiences. The male teachers appeared to perceive more positive than the female teachers towards the training effectiveness in both skill enhancement and training management. Non-graduate teachers perceived more positive than the graduate teachers towards training effectiveness in the dimension of training management. While the more experienced teachers perceived the training was effective in the skill enhancement as compared to the less experienced teachers.